Understanding exercise behavior among Tehran adolescent girls according - Khaniyan, Hadiseh; Hosseini, Meimanat; Atashzadeh Shorideh, Forozan; Chaibakhsh, Samira (Advances in Nursing & Midwifery, 2015)
Abstract ——————————————————————————————————————————- Background and aim: decline of exercise during adolescence especially in adolescent girls is documented. Nevertheless, there is relatively little understanding about exercise behavior and it’s mechanisms during adolescence. The purpose of this study is understanding exercise behavior among Tehran adolescent girls according to Stage of Change Model. Methods: This was a cross-sectional descriptive study that was conducted on 430 adolescent girls ranged in age from 14-17 years that were selected from Tehran daily public and private high school by multi stage sampling method. 2 questionnaires: demographics questionnaire and Stage of Exercise Change Questionnaire (SECQ) and 3 scales: Exercise Benefits/ Barriers Scale (EBBS), Self efficacy scale and Process of change scale were used for data collection and some of which was validated and made reliable. ANOVA accompanied by Tukey’s post hoc test were used for data analysis. Results: 30% of Tehran adolescent girls were in pre - contemplation stage. Totally 73.8% of samples were in pre- action stages (pre – contemplation, contemplation, preparation) and they were sedentary. All of the stage of change model’s constructs differed from pre - contemplation stage through maintenance stage significantly (p< 0.001). Adolescent girls in pre- contemplation scored the lowest and those in maintenance stage scored highest on self-efficacy, perceived benefits and process of change and reversed on perceived barriers. Conclusion: Results of recent study supported the use of stage of change model in understanding exercise behavior among adolescent girls and showed that the stage of change model can serve as a useful frame work to understand adolescent girl exercise behavior so using the stage of change model is recommended in understanding and promoting exercise behavior among adolescent girls. Keyword: Stage of Change Model, exercise behavior, adolescents, girls